2019
DOI: 10.1186/s13104-019-4088-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with diabetic foot among type 2 diabetes in Northern area of Saudi Arabia: a descriptive study

Abstract: ObjectiveFoot complications are considered to be a devastating consequence of type 2 diabetes mellitus (T2DM), posing a major medical and economic burden. A prospective study was conducted at researchers’ area “Northern area of Saudi Arabia” to determine the factors associated with diabetic foot (DF) among T2DM patients. Identifying the extent of this problem and the associated factors will enable the health providers to imply early preventive measurements.ResultsTwo hundred T2DM patients with/without DF (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
2
22
1
1
Order By: Relevance
“…The risk factors identified for the presence of DFUs were very similar to those identified in previous literature data, such as older age, poor glucose control, a high prevalence of diabetic neuropathy and a high prevalence of peripheral artery disease [ 22 , 23 , 24 , 25 , 26 ]. Coronary artery disease (CAD) had a significantly higher prevalence in patients with foot ulcerations, a fact frequently reported in literature, due to an aggregation of cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The risk factors identified for the presence of DFUs were very similar to those identified in previous literature data, such as older age, poor glucose control, a high prevalence of diabetic neuropathy and a high prevalence of peripheral artery disease [ 22 , 23 , 24 , 25 , 26 ]. Coronary artery disease (CAD) had a significantly higher prevalence in patients with foot ulcerations, a fact frequently reported in literature, due to an aggregation of cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 79%
“…Coronary artery disease (CAD) had a significantly higher prevalence in patients with foot ulcerations, a fact frequently reported in literature, due to an aggregation of cardiovascular risk factors. It is estimated that cardiovascular-related mortality and morbidity is two to four times higher in DM patients diagnosed with diabetic foot ulceration compared with those without ulcerations [25,26]. The relationship is bidirectional; firstly, hyperglycaemia, hypertension and dyslipidaemia contribute both to the development of CAD and diabetic foot ulceration; additionally, the presence of diabetic foot ulceration and the infection is associated with an inflammatory reaction, a subclinical inflammation characterised by high levels of circulating cytokines such as tumour necrosis factor (TNF) or interleukin 6 (IL-6), resistin, macrophage inflammatory protein-1β and low circulating levels of adiponectin [26,27]; these cytokines have a negative role on the normal function of the endothelium, thus increasing the risk for subsequent cardiovascular events [28].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the association of age and DFU was not significant. However, previous cross-sectional studies conducted in Thailand, 35 India, 36 and Saudi Arabia 34 showed older age to be significantly associated with DFU. This difference might be due to the current study considers only newly diagnosed diabetes patients and the majority 61% of the participants were younger than 50 years but in the former study, for example in Saudi Arabia, 34 the majority 66% of patients were older than 50 years.…”
Section: Discussionmentioning
confidence: 84%
“…[28][29][30][31] Studies indicated that DFU is affected by sociodemographic factors, clinical factors, and comorbidities. Among socio-demographic factors male sex, 32,33 being in the older age group, [34][35][36] and rural residency 28,31 are related to a higher risk of DFU. Of clinically related factors, duration of DM, 28,37 increased body mass index (BMI), 31,37 increased hemoglobin A1c (HgbA1c), 33,38 higher low-density lipoprotein (LDL), higher triglyceride level, and lower high-density lipoprotein (HDL) level [39][40][41][42] are associated with increased risk for vascular complication including DFU.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian yang dilakukan di Arab Saudi menunjukkan responden dengan kontrol glikemik yang buruk beresiko 4 kali lebih besar untuk mengalami kaki diabetic dibandingkan responden dengan kontrol glikemik yang baik 16 .…”
Section: Pembahasanunclassified